Who does an elite organization emulate? - Stell, Mary C.; Strang, David (2009)
We advance theories of the diffusion of innovations by examining the structure of emulation that emerged in one bank's benchmarking program. Prestigious firms and firms linked to the bank through executive migration were disproportionately likely to be recruited as benchmarking partners and, once visited, to be highly influential. Firms tied to the bank by board interlocks and geographic proximity were neither overrepresented nor influential. The bank also paid modest attention to other financial service providers, particularly rival money centres. These relationships hold net of area-specific recognition for excellence, which promotes attention but not influence, and financial performance, which affects neither. We emphasize the way organizational identity and decision-making processes activate and deactivate network ties as potential channels of innovation diffusion. - Reproduced.
Keywords: Organizations